A novel 18-bp in-frame deletion mutation in RUNX2 causes cleidocranial dysplasia. (December 2018) - Zeng, Li; Wei, Jiahui; Zhao, Na; Sun, Shichen; Wang, Yixiang; Feng, Hailan
Highlights: Our research group collected a novel de novo mutation of RUNX2 in a CCD patient, this patient showed typical CCD features. Conservation analysis revealed that the novel mutation located in the QA domain, while structure changes are located in the Runt domain. Functional analysis of the novel de novo mutation demonstrated that the loss of function in RUNX2 is responsible for CCD. Abstract: Objectives: Runt-related transcription factor 2 ( RUNX2 ) gene is known to cause rare autosomal dominant skeletal disorder Cleidocranial dysplasia (CCD). Here, we explored a novel, large deletion in RUNX2 gene in a Chinese patient with CCD and the function associated with the mutation. Design: Genomic DNA was extracted from the peripheral blood and subjected to do DNA sequencing. Sanger sequencing was used to do mutational analysis of the RUNX2 gene. Function associated with RUNX2 mutation was investigated by performing conservation analysis, secondary structure analysis, subcellular localization study and reporter assay. Results: We identified a novel, large deletion mutation involving a c.243-260del GGCGGCTGCGGCGGCGGC mutation in exon 2 of the RUNX2 gene. Conservation and secondary structure analysis revealed that the novel mutation located in QA domain and converted the structure of RUNX2. Subcellular localization analysis revealed that the novel mutant showed the same intracellular localization with the wild type of RUNX2, and both of them localized exclusively in the nucleus. While reporter assay indicated the novel mutant severely impaired the transactivation activities of RUNX2 gene. Conclusions: Our findings demonstrated that the novel c.243-260del GGCGGCTGCGGCGGCGGC mutation resulted in CCD. These results extend the spectrum of RUNX2 mutations in CCD patients and suggest a functional role of the novel mutation in CCD.